Acute effect of eccentric overload exercises on change of direction performance and lower-limb muscle contractile function - Beato, M.; Madruga-Parera, M.; Piqueras-Sanchiz, F.; Moreno-Pérez, V.; Romero-Rodriguez, D. (The Journal of Strength and Conditioning Research, 2021)
This study aimed to evaluate the postactivation potentiation (PAP) effects following eccentric overload (EOL) exercises on change of direction (COD) performance and muscle contractile function. Thirty-one male soccer players (age 21 ± 4 years; body mass 77.0 ± 5.2 kg) were involved in a cross-sectional study. Dominant-leg (COD-5mD) and non-dominant-leg (COD-5mND) shuttle tests were performed 4 minutes after the EOL exercises. Muscle contractile function was assessed by tensiomyography (TMG) such as muscle contraction time (Tc), time delay (Td) and displacement of the muscle belly (Dm) of vastus lateralis (VL), vastus medialis (VM), and rectus femoris (RF). Eccentric overload exercises were: (a) cross-cutting step with inertial conical pulley (INC = 11 subjects), (b) flywheel leg extension (EXT = 10 subjects), and flywheel yo-yo squat exercise (SQU = 10 subjects). Differences baseline-post were found on COD-5mD (p < 0.001) and on COD-5mND (p < 0.001), but not between groups (p > 0.05) following EOL exercises. Differences from baseline were found in VL Td (p < 0.001), VM Td (p = 0.003), RF Tc (p < 0.001), and RF Td (p < 0.001) with no significant differences between the EOL exercises. This study reported a significant positive PAP response on COD-5mD and COD-5mND after 4 minutes of recovery after EOL exercises (INC, EXT and SQU) in soccer players. For the first time, it has been reported that EOL exercises acutely affect TMG variables (e.g., Tc and Td) in lower limbs. Such results related to changes in muscular contractile functions may contribute to explain the physiological mechanisms (e.g., neuromuscular factors) associated with PAP effect.